New directions in social education research : the influence of technology and globalization on the lives of students - Maguth, Brad M., 1980- (Research in social education., 2012)
Through rapid developments in commerce, transportation and communication, people once separated by space, language and politics are now interwoven into a complex global system (Friedman, 2005). With the rise of new technology, local populations, businesses and states are better equipped to participate and act in a thriving international environment. Rising instability in the Middle East is immediately reported to oil and gas brokers in the U.S. Within seconds cable channels, iPods, social networking sites, and cell phones are relaying how protests in Egypt and Libya give hope to citizens around the world yearning for freedom. As events like 9/11 and the 2008 Financial Crisis have demonstrated, there is no retreating from the interconnectedness of the global system. As societies strive to empower citizens with the skills, understandings and dispositions needed to operate in an interconnected global age, teachers are being encouraged to help students use technologies to develop new knowledge and foster cross cultural understandings.As pressures mount for society to equip today's youth with both the global and digital understandings necessary to confront the challenges of the 21st century, a more thorough analysis must be undertaken to examine the role of technology on student learning (Peters, 2009). This work will highlight the complex, contested, and contingent ways new technologies are being used by today's youth in a digital and global age. This text will present audiences with in-demand research that investigates the ways in which student use of technology mediates and complicates their learning about the world, its people, and global issues.